1995
DOI: 10.1111/j.1476-5381.1995.tb13275.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of NMDA effects on agonist‐stimulated phosphoinositide turnover by memantine in neonatal rat cerebral cortex

Abstract: 1 The ability of memantine (l-amino-3,5-dimethyladamantane)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…The lack of inhibitory effect of Mem on VCM development during treatment supports the assumption that different mechanisms may underlie transient and persisting VCM (Andreassen & J0rgensen, 1994;1995b). Mem is a non-competitive, open channel blocker of the NMDA-receptor cation channel (Bormann, 1989;Chen et al, 1992;Parsons et al, 1993;Mistry et al, 1995), and the protective effect of Mem demonstrated in the present study is in all probability due to its NMDA antagonism. In other studies a protective effect of Mem against NMDA receptor-mediated neurotoxicity has been found both in vitro and in vivo (reviewed by Kornhuber et al, 1994).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The lack of inhibitory effect of Mem on VCM development during treatment supports the assumption that different mechanisms may underlie transient and persisting VCM (Andreassen & J0rgensen, 1994;1995b). Mem is a non-competitive, open channel blocker of the NMDA-receptor cation channel (Bormann, 1989;Chen et al, 1992;Parsons et al, 1993;Mistry et al, 1995), and the protective effect of Mem demonstrated in the present study is in all probability due to its NMDA antagonism. In other studies a protective effect of Mem against NMDA receptor-mediated neurotoxicity has been found both in vitro and in vivo (reviewed by Kornhuber et al, 1994).…”
Section: Discussionsupporting
confidence: 84%
“…However, the NMDA antagonist, memantine (Mem), is used clinically in the treatment of Parkinson's disease and spasticity and is well tolerated (Weseman et al, 1983;Schneider et al, 1984). It is a non-competitive, open channel blocker of the NMDA-receptor cation channel (Bormann, 1989;Chen et al, 1992;Parsons et al, 1993;Mistry et al, 1995), which protects against excitotoxic neurodegeneration (reviewed in Kornhuber et al, 1994). Mem is proposed as a candidate for long-term neuroprotection in chronic neurodegenerative diseases (Lipton, 1993;Rogawski, 1993 (Oil; Nycomed Pharma, Norway).…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been reported that memantine does not affect CCh-induced IP 3 production in neonatal rat cerebral cortex slices [29]. This is in agreement with our own results, and implies that the potentiating effect of memantine on agonistinduced Ca 2+ release is mediated by a mechanism that does not involve the either potentiation of IP 3 production or IP 3 R activity.…”
Section: Discussionsupporting
confidence: 82%
“…In cats perfused with amantadine, 418 an increase in preloaded dopamine was observed; other in vivo studies to show a modest and highly variable effect of Aminoadamantanes on the dopaminergic system likewise use extremely high, clinically irrelevant concentrations of the drugs and are, therefore, considered not reliable for the elucidation of the primary MOA of these drugs. 419421 The NMDA-receptor antagonism was more and more considered to be a result of open-channel block of the receptor's pore, as the aminoadamantanes are strongly voltage-dependent antagonists. 38,422,423 The difference in activities between amantadine and memantine found in various brain regions strikingly parallels the NMDA-receptor induced acetylcholine release in these areas (here: Amantadine has higher activity in striatal slices when compared to hippocampal slices).…”
Section: Adamantanes Against Diseases Of the Central Nervous Systementioning
confidence: 99%